Bending Moment Characteristics of Hard Roof before First Breaking of Roof Beam Considering Coal Seam Hardening - Shitan Gu; Bangyou Jiang; Yue Pan; Zheng Liu (Shock and Vibration)
The mechanical properties of a coal seam affect the distribution of support pressure. Considering the strain hardening effect of coal seam, the support pressure relationship of three zones—softened, hardened, and elastic—of a coal seam with regard to a hard roof is proposed, and methods to determine an approximate expression for the support pressure of hardened zone of coal seam, the range of hardened zone, and the corresponding peak values of support pressure are provided. The deflection equations of a hard roof under three different support pressure relationships of coal seam before the first breaking were theoretically derived, and all the relevant integration constants were determined. Numerical examples of two cases are provided for calculating the bending moment of a hard roof and the support pressure of a coal seam. The analysis shows that as the working face advances, the maximum support pressure increases, the residual strength of coal seam at coal wall decreases, the overall deflection of roof gradually increases, the maximum bending moment of roof in the front of coal wall increases, and the advanced distance of roof bending moment peak gradually increases. As the depth of softened zone of coal seam increases, the similar conclusion is obtained, and the advanced distance of the roof bending moment peak increases at a relatively fast speed. Because the bending moment peak of hard roof is located near the support pressure peak in the softened zone of coal seam, the depth of softened zone of coal seam significantly affects the advanced distance of the bending moment peak of a roof. The actual advanced fracture distances of hard roof are distributed in a relatively broad range. The results indicate that there is a “large and long” type advanced fracture distance occurring in the actual stope. With the same overlying load and stope parameter conditions, the maximum support pressures of support roof in softened, hardened, and elastic zones considering a hardened coal seam are smaller than those in softened and elastic zones without hardening. However, the plumpness in front of the peak of the former support pressure curve is superior to that of the latter, and both the bending moment peak value and the advanced distance of bending moment peak of the former are higher than those of the latter.